A Trial of Oil-Adjuvant Influenza Vaccine in a Non-Epidemic Season. Issue 4 (October 1964) - Howell, R. W.; Stott, A. N. B.
Abstract : In the autumn of 1963, 1, 679 employees at two U.K.A.E.A. establishments were inoculated with a single dose (0·25 ml.) of polyvalent oil-adjuvant influenza vaccine. In a non-epidemic winter, no significant improvement in certified sickness absence could be demonstrated in the vaccinated group when compared with a randomly selected uninoculated group. In particular, no real protection was shown, in those vaccinated, against influenza and acute upper respiratory tract infections. Once respiratory sickness had occurred the vaccine showed no significant effect on the length of sickness absence. In this trial, unpleasant reactions to the vaccine occurred in about a quarter of the inoculated, and, in particular, a large number of participants complained of general malaise which persisted for more than two weeks. These reactions were thought to be severe enough to induce consumer resistance to routine annual immunization, which is thought to be neither justified nor acceptable in a healthy industrial population at the present stage of vaccine development. This in no way detracts from the suitability or acceptability of the vaccine to high-risk patients. Further research and testing, which is being carried out by pharmaceutical firms, is essential, and so, too, is the need for more controlled trials to evaluate changing vaccines in different population groups.